THE RELATIONSHIP BETWEEN MOTIVATION MOTHERS PROVIDE BALANCED NUTRITION TO THE GROWTH AND DEVELOPMENT OF CHILDREN IN THE VILLAGE JATIWATES TEMBELANG DISTRICT OF JOMBANG - Renov Terra J.; Inayatur Rosyidah; . Badri (STIKES Insan Cendekia Medika Jombang, 2012)
Nutrition is very important to support the various activities of daily life. Problems of malnutrition can not beseparated from the nutrients consumed. Until today many mothers who do not know about balancednutrition, so less motivated to dig up information about the type, processing and presentation of goodnutrition to children. The aim of research to analyze the relationship between motivation mothers providebalanced nutrition to the growth and development of children in the village Jatiwates Tembelang District ofJombang.This type of research is an analytic cross-sectional, population is all Mother who has particularlychildren in the village Jatiwates District of Tembelang Jombang in 2012 some 224 people, with a sample of144 people with engineering cluster random sampling, independent variables maternal motivation providebalanced nutrition, the dependent variable of growth and early childhood development. Collecting data usingKMS and KPSP, data analysis using the Spearman rank test. The results showed nearly half (48.6%)maternal motivation in providing balanced nutrition is strong as many as 70 people, moderate growth ofmore than half (54.9%) infant growth are good as much as 79 people, the development shows the majority(75.7%) of early childhood development is appropriate as many as 109 people. Spearman rank testcorrelation between motivation with growth of infants is = 0.000 <0.05 then there is a relationship H1accepted and spearman rank test correlation between motivation with development of infants is = 0.012<0.05 then there is a relationship H1 accepted. It can be concluded that with the strong motivation inproviding balanced nutrition, the growth and development of infants accordingly.